Frequency of Hypocalcemia and Hypomagnesemia in Autistic Spectrum Disordered Children of Bangladesh (Journal of Rangpur Medical College, 2024)
Background: Autistic spectrum disorder (ASD) in children is commonly associated with mitochondrial dysfunction and mineral deficiency. Studies have highlighted links between Ca2+ and Mg2+ deficiency and neuronal excitability, along with connections between iron deficiency and behavioral abnormalities in individuals with ASD. Objective: This study was aimed to assess the frequency of hypocalcemia and hypomagnesemia in autistic spectrum-disordered children of Bangladesh. Methods: This cross-sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University, Dhaka from March 2014 to January 2015. The study included 100 randomly selected male children, with 50 in a healthy control group (Group A) and 50 diagnosed with autistic spectrum disorder (Group B). Children with ASD were selected from the Parents Forum (DOHS, Mohakhali), while the control group was chosen from schools with typically developing children. Fasting serum levels of various components along with calcium and magnesium were measured, and statistical analysis was conducted using independent sample 't' tests and proportion (Z) tests, with a significance level set at p-value ˂0.05. Results: In this study, out of 50 autistic spectrum disorder cases, the frequencies of hypocalcemia and hypomagnesemia were 74% and 52%, respectively. A comparison with the control group revealed significantly higher frequencies of both hypomagnesemia and hypocalcemia in the ASD group, with p-values